Effect of seed coating with biological agents on seed quality of rice - TANTRI PALUPI; SATRIYAS ILYAS; MUHAMMAD MACHMUD; ENY WIDAJATI (Society for Indonesian Biodiversity, 2017)
Palupi T, Ilyas S, Machmud M, Widajati E. 2017. Effect of seed coating with biological agents on seed quality of rice. Biodiversitas 18: 727-732. The research that consisted of two activities was performed at the Laboratory. Experiment 1 the aim to obtain biological agents that have high antagonistic potential against Xanthomonas oryzae pv. oryzae (Xoo) and two biological agents that are compatible to one another. Experiments 2 to determine the effect of rice (Oryza sativa L.) seeds coated with biological agents to improve seed quality and reduce levels of Xoo infection. In the first experiment, four isolates of bacterial antagonists, i.e: isolate Pseudomonas diminuta A6; isolate P. aeruginosa A54; isolate Bacillus subtilis 11/C, and isolate B. subtilis 5/B, were tested for their antagonism activities against Xoo on PSA plates using the method of growth inhibition zone with filter paper. Furthermore, the four antagonists were tested for their compatibility with each other on PSA plates. In the second experiment used a completely randomized design with a single factor (seed coating) consisting of seven levels, namely: negative control, healthy seed; positive control, the seeds contaminated with Xoo; P. diminuta A6 and B. subtilis 5/B; alginate 3% + 1% peat + P. diminuta A6 and B. subtilis % 5/B; arabic gum 3% + 1% gypsum + P. diminuta A6 and B. subtilis 5/B; CMC 1.5% + 1% talc + P. diminuta A6 and B. subtilis 5/B, and bactericide streptomycin sulfate 20%. Results of Experiment 1 showed that isolates P. diminuta A6 has the highest antagonistic potential against Xoo based on the diameter of inhibition zone on Xoo, followed by isolate B. subtilis 5/B. Isolate P. diminuta A6 and B. subtilis 5/B had a good growth compatibility with no antagonism. Therefore, isolates P. diminuta A6 and B. subtilis 5/B were selected and used as biocontrol agents in further studies. Results of Experiment 2 showed that treatment with P. diminuta A6 + B. subtilis 5/B gave the best of the increase of seed vigor, and the decrease of Xoo infection level in the seeds.